2005
DOI: 10.1128/jb.187.20.6917-6927.2005
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of Cyclic Enterobacterial Common Antigen in Escherichia coli K-12

Abstract: We describe here the purification and quantification of a water-soluble cyclic form of enterobacterial common antigen (ECA CYC ) from Escherichia coli K-12 as well as information regarding its subcellular location and the genetic loci involved in its assembly. Structural characterization of purified ECA CYC molecules obtained from E. coli K-12 revealed that they uniformly contained four trisaccharide repeat units, and they were substituted with from zero to four O-acetyl groups. Cells from overnight cultures c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
82
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(86 citation statements)
references
References 40 publications
4
82
0
Order By: Relevance
“…ECA is found in many genera of the Enterobacteriaceae (53). Wzz E participates in the biosynthesis of both ECA PG (4), a phosphoglyceride-linked form, and ECA CYC (45), an unusual cyclic molecule containing four to six ECA repeat units. In the absence of any detailed characterization of the PCP proteins associated with group E OPX proteins, we have retained the PCP-1 designation.…”
Section: Erwinia Amylovora Escherichia Coli -Colanic Acidmentioning
confidence: 99%
“…ECA is found in many genera of the Enterobacteriaceae (53). Wzz E participates in the biosynthesis of both ECA PG (4), a phosphoglyceride-linked form, and ECA CYC (45), an unusual cyclic molecule containing four to six ECA repeat units. In the absence of any detailed characterization of the PCP proteins associated with group E OPX proteins, we have retained the PCP-1 designation.…”
Section: Erwinia Amylovora Escherichia Coli -Colanic Acidmentioning
confidence: 99%
“…A water-soluble cyclic form of ECA (ECA CYC ) has also been demonstrated to be present in many gram-negative enteric bacteria (7,14,28,48), and the available data suggest that ECA CYC may indeed occur in all members of the Enterobacteriaceae (19). Recent studies have demonstrated that ECA CYC is located exclusively in the periplasm of Escherichia coli K-12, and cells from cultures grown overnight were found to contain approximately 2 g of ECA CYC (dry weight) per milligram (19).…”
mentioning
confidence: 99%
“…Recent studies have demonstrated that ECA CYC is located exclusively in the periplasm of Escherichia coli K-12, and cells from cultures grown overnight were found to contain approximately 2 g of ECA CYC (dry weight) per milligram (19). Structural characterization of the ECA CYC molecules isolated from E. coli K-12 revealed that they uniformly consist of four trisaccharide repeat units, and each molecule of ECA CYC contains from zero to four O-acetyl groups (15,19). Similar to ECA PG , the O-acetyl groups of ECA CYC are also linked to the 6 position of GlcNAc residues (14).…”
mentioning
confidence: 99%
“…It was particularly dramatic in wzzE and the downstream wecB-wecA genes. These genes encode for ECA chain length regulatory protein and for enzymes required for the biosynthesis of ECA glycosyl precursors, respectively (Barr et al, 1999;Kajimura et al, 2005). The immunoblotting analyses of the present work suggested coexistence of OPS and ECA in the Y. enterocolitica O : 3 LPS.…”
Section: Eca and Ops Coexist In The Lps Of Y Enterocolitica O :mentioning
confidence: 55%
“…This polymer can either covalently anchor to the outer membrane via its own L-glycerophospholipid (ECA PG ) or utilize in some bacteria the core oligosaccharide as an attachment point (ECA LPS ). The third form of ECA, found in the periplasmic space, is a cyclic form and has no lipid anchor (ECA CYC ) (Kajimura et al, 2005;Kuhn et al, 1988;Lugowski et al, 1983). Of these three ECA types, only ECA LPS is naturally immunogenic and it has been detected from Escherichia coli, Proteus mirabilis and Yersinia enterocolitica Kasperkiewicz et al, 2004;Kuhn et al, 1988;Rabsztyn et al, 2011;Radziejewska-Lebrecht et al, 2003).…”
Section: Introductionmentioning
confidence: 99%